Second-Line Treatment for Pancreatic Cancer - Kaddis, Nancy; Saif, Muhammad Wasif (JOP. Journal of the Pancreas, 2014)
Although standard of care for treatment of pancreatic cancer is established in the first line setting, there is limited data to support standard for second line chemotherapy for advanced pancreatic cancer. This is starting to change, as new studies have shown positive effect on overall survival in the second line setting. At the recent ASCO Annual Meeting 2014, several new second-line chemotherapy regimens were presented, including ruxolitinib with capecitabine, oxaliplatin with 5-FU/leucovorin, metformin plus paclitaxel and gemcitabine plus nab-paclitaxel. These abstracts provide exciting new directions for the second line treatment of advanced pancreatic cancer that has been refractory to both gemcitabine-based regimens as well as non-gemcitabine based regimens. Image: Schematic representation of the mechanism of action of the Janus kinase inhibitors.